Maternal Perceptions of Self-Weight and Child Weight May Influence Milk Choice of Participants in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) - Loan P. Kim; Nelly Mallo (Journal of Obesity)
Objective. To examine the association between maternal perceptions of self-weight and child weight status and milk consumption behavior of Hispanic WIC participants. Methods. Mixed methods design with phone survey (n=529) and one-on-one interviews (n=35). Demographic characteristics, Chi-square, and thematic analyses were conducted. Results. More than half of overweight mothers misperceived their own weight status as well as those of their children. Mothers who perceived their child to be overweight were more likely to make a healthier food choice for their family, namely, choosing reduced-fat milk instead of whole milk. Qualitative interviews revealed a cultural preference for larger size children, and mothers defined healthy weight for their child as a function of (1) the child’s ability to be as active as other children their age, regardless of child’s BMI, and (2) the pediatrician’s opinion of the child’s weight status. Conclusions. Maternal perception of self-weight and child weight status seems to guide milk choices. Mothers may have some level of recognition of overweight in themselves and their child, thus adopting healthier milk choices. Culturally related perceptions should be considered when designing obesity prevention strategies, and the role of a pediatrician cannot be understated when developing obesity prevention programs for Hispanic families.